2017
DOI: 10.1093/jxb/erx061
|View full text |Cite
|
Sign up to set email alerts
|

The 2′-O-methyladenosine nucleoside modification gene OsTRM13 positively regulates salt stress tolerance in rice

Abstract: Highlight OsTRM13 is a 2′-O-methyladenosine tRNA nucleoside modification gene that positively regulates salt stress tolerance in rice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 66 publications
1
26
0
Order By: Relevance
“…7a, and b ). In a recent study, we have shown that abscisic acid (ABA) treatment also induced a significant increase of Am nucleosides in rice seedlings [ 28 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…7a, and b ). In a recent study, we have shown that abscisic acid (ABA) treatment also induced a significant increase of Am nucleosides in rice seedlings [ 28 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Small RNAs (< 200 bp) were extracted using microRNA Extraction Kit (Omega Bio-tek Inc.), digested into nucleosides and analyzed by LC-MS/MS with an LC-20A HPLC system and a diode array UV detector (190-400 nm). Details for LC-MS/MS analysis was described previously [ 28 ]. The abundance of each nucleoside under stress conditions was normalized to that in control set, the ratio (fold of change) of each nucleoside was calculated and used for heatmap generation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the past few decades, with the continuous development of biological technologies and high-throughput sequencing technologies (Goff et al 2002;Yu et al 2002;International Barley Genome Sequencing Consortium et al 2012;International Wheat Genome Sequencing Consortium et al 2014;Schnable et al 2009), more and more researchers have been able to identify and clone genes or transcription factors related to stress resistance in these crops (Mickelbart et al 2015;. As a large number of genes and transcription factors were found to be related to the stress resistance of crops (Güre et al 2016;Barnawal et al 2017;Wang et al 2017;Gao et al 2018),researchers published the research results through the display of articles in major academic journals for reference by other researchers. Mass research were scattered across different journals' websites or public document data websites.…”
Section: Introductionmentioning
confidence: 99%